Financial Network Systemic Risk Contributions - Hautsch, Nikolaus; Schaumburg, Julia; Schienle, Melanie (Review of Finance, 2015)
We propose the realized systemic risk beta as a measure of financial companies’ contribution to systemic risk, given network interdependence between firms’ tail risk exposures. Conditional on statistically pre-identified network spillover effects and market and balance sheet information, we define the realized systemic risk beta as the total time-varying marginal effect of a firm’s Value-at-risk (VaR) on the system’s VaR. Statistical inference reveals a multitude of relevant risk spillover channels and determines companies’ systemic importance in the US financial system. Our approach can be used to monitor companies’ systemic importance, enabling transparent macroprudential supervision.